Infrared studies of surface carbonate binding to diimine-tricarbonyl Re(I) and Mn(I) complexes in mesoporous silica. Issue 8 (18th April 2019) - Louis, Michael E.; Li, Gonghu
Abstract: Diimine-tricarbonyl Re(I) and Mn(I) complexes have demonstrated interesting activity in photocatalytic and electrochemical CO2 reduction. In this study, we take a surface chemistry approach to investigate interactions of CO2 with Re(I) and Mn(I) complexes in the presence of triethylamine. The molecular complexes were adsorbed on the surface of a mesoporous silica. Under dark conditions, formation of metal-carbonate adducts was observed by infrared spectroscopy in the presence of CO2, triethylamine, and surface silanol groups. The Langmuir adsorption model was utilized to extract quantitative information regarding surface carbonate binding to the two molecular complexes. The results indicate that binding of carbonate was much stronger on the Re(I) center than on Mn(I), consistent with prior observations regarding the relative activities of these complexes in CO2 -reduction catalysis. Abstract :